2007
DOI: 10.1177/0258042x0703200306
|View full text |Cite
|
Sign up to set email alerts
|

Role of Infrastructure Services on the Economic Development of India

Abstract: The importance of infrastructure for sustained economic development is well recognized. High transaction costs arising from inadequate and inefficient infrastructure can prevent the economy from realising its full growth potential regardless of the progress on other fronts. Physical infrastructure covering transportation, power and communication through its backward and forward linkages facilitates growth, social infrastructure including water supply, sanitation, sewage disposal, education and health, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The role of infrastructure is multifaceted. Infrastructure is categorized as physical (Singh et al 2007) and social (Ramani and Mavalankar 2006;Pal 2010). 1 It provides the means to public policy in stimulating national or regional development, as well as subsequent regional economic convergence (Button 1998).…”
Section: Infrastructurementioning
confidence: 99%
“…The role of infrastructure is multifaceted. Infrastructure is categorized as physical (Singh et al 2007) and social (Ramani and Mavalankar 2006;Pal 2010). 1 It provides the means to public policy in stimulating national or regional development, as well as subsequent regional economic convergence (Button 1998).…”
Section: Infrastructurementioning
confidence: 99%
“…Governments around the globe used to be only investors in public infrastructure for centuries. Responsibilities for construction, implementation, operation, maintenance and further repair of infrastructure were with governments (Guptaand, Sravat, 1998;Singh, et. al., 2007).…”
Section: Figurementioning
confidence: 99%
“…Physical or so called economic infrastructure is responsible for subsectors, which are directly linked to production and economic activities (Ghoshand, 1998;Majumder, 2010;Singh, et. al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In every nation, government seeks to protect the consumer's interest and maintaining a modern regulatory system. According (Shailender Singh , et al, 2017) study revealed that improving infrastructure will boost economic growth and attract more foreign direct investment and will also improve the welfare of the society.…”
Section: Introductionmentioning
confidence: 99%